Impact of ciprofloxacin, carbamazepine and ibuprofen on a membrane bioreactor system: Kinetic study and biodegradation capacity. Issue 12 (7th June 2017) - Calero‐Díaz, Gustavo; Monteoliva‐García, Antonio; Leyva‐Díaz, Juan Carlos; López‐López, Cristina; Martín‐Pascual, Jaime; Torres, Juan Carlos; Poyatos, José Manuel
Abstract: BACKGROUND: This study analyzed the effects of carbamazepine, ciprofloxacin and ibuprofen on the behavior of a membrane bioreactor (MBR) system treating urban wastewater that was doped continuously with three different concentrations of this mix of pharmaceuticals under a hydraulic retention time of 6 h. RESULTS: The degradation capacity of these chemicals and the heterotrophic kinetics regarding the organic matter removal were evaluated in the control and doping cycles. CONCLUSIONS: Although the MLSS decreased drastically, these differences were not observed in the organic matter removal as the increase of cell growth rate cancelled out the increase in cell decay rate due to the chemical stress caused by the addition of pharmaceuticals, as shown by the increased organic matter degradation rate from 86.27 mgO2 L −1 h −1 in the control cycle to values within the limits 183.97 mgO2 L −1 h −1 and 192.88 mgO2 L −1 h −1 in doping cycles. The degradation rates were 0.0154, 0.0152 and 0.0160 μgS/((μgSin /L)*h*mgMLSS) for carbamazepine, ciprofloxacin and ibuprofen, respectively, involving removal yields higher than 71.9, 88.7 and 94.7% for carbamazepine, ciprofloxacin and ibuprofen, respectively, at the three different concentrations tested. Therefore, MBR technology can be used as a reliable process to significantly reduce this mix of pharmaceuticals without reducing its organic matter removal capacity. © 2017 Society of Chemical Industry